An Integrated Legal Framework for Digital Investment Fraud Prevention in Indonesia - Halomoan Napitupulu, Josua; L. Panggabean , Mompang; Panjaitan, Hulman; Sri Widiarty , Wiwik (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
The rapid development of digital financial technology in Indonesia has presented significant opportunities for investment growth, but has also opened up space for increasingly complex fraudulent methods. The significant public losses due to illegal digital investments demonstrate that the existing legal framework is unable to provide effective protection, as regulations remain fragmented, repressive, and not fully adaptable to technological innovation. This study aims to identify an integrated legal framework for preventing digital investment fraud. The research method employed is normative juridical research, utilizing a statutory and conceptual approach, as well as a comparison with Singapore, which is recognized for its responsive legal framework to developments in financial technology. The results show that existing provisions, such as the Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE), have proven inadequate because they are designed to address conventional fraud or electronic information fraud in general, not the complexities of digital investment. This situation creates legal uncertainty, making it difficult for law enforcement officials to accurately classify crimes and impose appropriate sanctions, while also weakening the legal protection for victims. In contrast, Singapore has been able to establish a responsive, consistent, and effective system for preventing and prosecuting digital investment fraud through the Securities and Futures Act (SFA) and the Monetary Authority of Singapore's (MAS) broad powers, encompassing regulation, investigation, and enforcement, with court support that provides a deterrent effect. Therefore, Indonesia needs to establish a more comprehensive, integrated, and specific regulatory framework for fraudulent investment crimes, encompassing prevention, law enforcement, victim protection, and recovery.